Association of Helicobacter pylori Infection with Coronary Artery Disease: Is Helicobacter pylori a Risk Factor? - Jamshid Vafaeimanesh; Seyyed Fakhroldin Hejazi; Vahid Damanpak; Mostafa Vahedian; Mohammadamin Sattari; Mohammadreza Seyyedmajidi (The Scientific World Journal)
Background. Helicobacter pylori (HP) infection is the most common infection in the world and coronary artery disease (CAD) is probably associated with it. The aim of this prospective study was to evaluate the association between HP infection and CAD in suspected patients referred for coronary angiography. The coronary angiography was performed using Judkins method and patients were assigned to participate in CAD positive (>50% luminal diameter stenosis) and negative groups. The serum HP IgG antibody was checked. Results. Positive and negative CAD groups consisted of 62 and 58 patients, respectively. HP was more prevalent among CAD+ patients, and with increasing the number of coronary arteries with stenosis, the HP seropositivity increased so that 76.3% of patients with multiple vessel diseases (MVD) and 70% of patients with single vessel diseases (SVD) were HP seropositive versus 50% in control group (P=0.006). Positive CAD was significantly associated with HDL level (P=0.01) and ESR level (P=0.006). Also, CAD+ patients had higher CRP levels than controls and it was statistically different between SVD group and controls (P<0.05). Conclusion. HP infection is more prevalent in CAD positive patients and, in case of proving causal relationship, it can be considered as a reversible risk factor for CAD.